Implementation of Regional Parking Regulations in Kabupaten Banyumas: A State Administrative Law Perspective on the “City of a Thousand Parking Spots” Phenomenon - Hariadi, Wahyu; Supriyo, Doni Adi; Anindito, Teguh (IJOSPOL - International Journal of Social, Policy and Law, 2026)
Parking management plays a strategic role in regional governance, as it relates to traffic order, public services, and local revenue generation. In Banyumas Regency, the rapid growth of urban activities, particularly in Purwokerto, has led to the proliferation of parking points, popularly known as the “city of a thousand parking spots.” While this reflects economic vitality, it also raises concerns regarding legality, tariff consistency, and administrative supervision in the implementation of Regional Regulations on parking. This research employs a normative legal method using statutory and conceptual approaches. The statutory approach examines the legal framework governing parking management, while the conceptual approach applies the principles of State Administrative Law, especially the principle of legality and the General Principles of Good Governance, as analytical benchmarks. Data were collected through library research and analyzed qualitatively using deductive reasoning. The study finds that although parking management in Banyumas Regency has a formal legal basis, discrepancies remain between regulatory provisions and field practices, particularly in tariff application and supervision. Effective parking governance therefore requires not only valid regulations but also consistent implementation aligned with principles of legality, transparency, accountability, and legal certainty to ensure public trust and sustainable regional revenue.